Meta-analysis and machine learning-augmented mixed effects cohort analysis of improved diets among 5847 medical trainees, providers and patients. Issue 2 (28th February 2022) - Monlezun, Dominique J; Carr, Christopher; Niu, Tianhua; Nordio, Francesco; DeValle, Nicole; Sarris, Leah; Harlan, Timothy
Abstract: Objective: We sought to produce the first meta-analysis (of medical trainee competency improvement in nutrition counseling) informing the first cohort study of patient diet improvement through medical trainees and providers counseling patients on nutrition. Design: (Part A) A systematic review and meta-analysis informing (Part B) the intervention analysed in the world's largest prospective multi-centre cohort study on hands-on cooking and nutrition education for medical trainees, providers and patients. Settings: (A) Medical educational institutions. (B) Teaching kitchens. Participants: (A) Medical trainees. (B) Trainees, providers and patients. Results: (A) Of the 212 citations identified ( n 1698 trainees), eleven studies met inclusion criteria. The overall effect size was 9·80 (95 % CI (7·15, 12·45) and 95 % CI (6·87, 13·85); P < 0·001), comparable with the machine learning (ML)-augmented results. The number needed to treat for the top performing high-quality study was 12. (B) The hands-on cooking and nutrition education curriculum from the top performing study were applied for medical trainees and providers who subsequently taught patients in the same curriculum ( n 5847). The intervention compared with standard medical care and education alone significantly increased the odds of superior diets (high/medium v . low Mediterranean diet adherence) for residents/fellows most (OR 10·79, 95 % CI (4·94, 23·58); P < 0·001) followed by students (OR 9·62, 95 % CI (5·92, 15·63); P < 0·001), providers (OR 5·19, 95 % CI (3·23, 8·32), P < 0·001) and patients (OR 2·48, 95 % CI (1·38, 4·45); P = 0·002), results consistent with those from ML. Conclusions: The current study suggests that medical trainees and providers can improve patients' diets with nutrition counseling in a manner that is clinically and cost effective and may simultaneously advance societal equity.